Effect of Printing Direction and Post-Printing Conditions on Bending Properties of ULTEM 9085 - Glaskova-Kuzmina, Tatjana; Dejus, Didzis; Jatnieks, Janis; Kruuv, Partel-Peeter; Zolotarjovs, Aleksejs; Einbergs, Ernests; Vanags, Edgars (MDPI, 2023)
The purpose of this study was to reveal the effect of printing direction and post-printing conditions on static and fatigue bending characteristics of Ultem 9085 at two stress levels. Right after the printing, the Ultem samples were subjected to three cooling conditions: cooling in the printer from 180 to 45 °C for 4 h, rapid removal from the printer and cooling in the oven from 200 to 45 °C during 4 h, and removal from the printer and cooling at room temperature. Static 3-point bending tests were performed to estimate the flexural characteristics of Ultem 9085 samples after subjecting them to different post-printing conditions. The flexural strain was evaluated and applied for the stress ratios such as 75% and 50% of σmax. Thus, displacement-controlled fatigue tests were carried out to reveal the effect of post-printing conditions on fatigue bending characteristics. The results obtained for the X and Y printing directions proved that the Ultem samples subjected to the cooling conditions in the printer and the oven had a similar static and fatigue behavior, while a lower performance was obtained for the samples cooled at room temperature. Regardless of the cooling regime, significantly lower bending performance was revealed for the samples printed in the Z-direction since they have intra-layer filaments parallel to the stress plane, and, accordingly, intra-layer adhesion has a crucial influence on mechanical performance. --//-- This is an open access article Glaskova-Kuzmina, T.; Dejus, D.; Jātnieks, J.; Kruuv, P.-P.; Zolotarjovs, A.; Einbergs, E.; Vanags, E. Effect of Printing Direction and Post-Printing Conditions on Bending Properties of ULTEM 9085. J. Compos. Sci. 2023, 7, 316. https://doi.org/10.3390/jcs7080316 published under the CC BY 4.0 licence.
This research was funded by the European Regional Development Fund within Measure 1.1.1.1 “Industry-Driven Research” of the Specific Aid Objective 1.1.1 “To increase the research and innovation capacity of scientific institutions of Latvia and their ability to attract external funding by investing in human resources and infrastructure” of the Operational Program “Growth and Employment” (Project No. 1.1.1.1/20/A/188). T.G.-K. is grateful to COST Action CA21155—Advanced Composites under High Strain Rates loading: a route to certification-by-analysis (HISTRATE). A.Z., E.E., and E.V. are grateful for funding received from the European Union Horizon 2020 Framework program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Ultem 9085; fused filament fabrication; thermal history; cooling conditions; mechanical properties; fatigue